Using an ethnography of email to understand distributed scientic collaborations - Sharma, S; Willis, M; Snyder, J; Osterlund, C; Sawyer, S (Illinois Digital Environment for Access to Learning and Scholarship, 2015)
In this brief poster abstract we explore the finding from previous research that distributed teams collaborating on research use email to an overwhelming degree. This email is the source of collaboration and one of the central documents in the practice of doing science. We present an early idea of email focused ethnography and using visualizations to assist in the qualitative exploration of analyzing email communications. Of interest is the utility of different visualizations to inform follow up interviews of longitudinal fieldwork and data collection. Two such visualizations are presented and described. Along with the benefits of the techniques we describe some of the challenges.